2019
DOI: 10.1373/clinchem.2018.299727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoked Cannabis on Vigilance and Accident Risk Using Simulated Driving in Occasional and Chronic Users and the Pharmacokinetic–Pharmacodynamic Relationship

Abstract: BACKGROUND The pharmacokinetic–pharmacodynamic relationship between whole blood δ-9-tetrahydrocannabinol (THC) and driving risk is poorly understood. METHODS Fifteen chronic cannabis consumers (1–2 joints/day; CC) and 15 occasional cannabis consumers (1–2 joints/week; OC) of 18 to 34 years of age were included. A pharmacokinetic study was conducted with 12 blood samplings over a 24-h period before and after controlled random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 40 publications
3
35
0
7
Order By: Relevance
“…The present study also demonstrated that cannabis increased subjective high and decreased performance on a sustained attention task in OUs, outcome variables previously found to be affected by cannabis (10, 31, 32). Furthermore, behavioral outcomes correlated with striatal functional connectivity to other areas of the reward circuit.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study also demonstrated that cannabis increased subjective high and decreased performance on a sustained attention task in OUs, outcome variables previously found to be affected by cannabis (10, 31, 32). Furthermore, behavioral outcomes correlated with striatal functional connectivity to other areas of the reward circuit.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore a priori ROI-to-ROI analysis assessed differences in connectivity strength between areas of the reward circuit. Finally, subjective high and sustained attention, two outcome variables shown to be modulated by (acute) cannabis exposure (10, 31, 32), were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…10,29,30 Furthermore a priori ROI-to-ROI analysis assessed differences in connectivity strength between areas of the reward circuit. Finally, subjective high and sustained attention, two outcome variables shown to be modulated by (acute) cannabis exposure, 10,31,32 were assessed.…”
Section: Introductionmentioning
confidence: 99%
“…They also agreed that lowering the legal limits of blood alcohol concentration (BAC) would lower the likelihood of accidents. Newest studies were similarly performed for cannabis in [92] and [93].…”
Section: A Driver Studiesmentioning
confidence: 99%